Pengaruh Pembiayaan Bagi Hasil Dan Pembiayaan Sewa Terhadap Laba Bersih PT. Bank Syariah Mandiri - Siti Aisyah Siregar (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2021)
Abstract: Based on the type of problem studied, the research approach used is associative. The data collection technique used is the study of documentation by collecting data derived from the monthly financial statements of PT Bank Syariah Mandiri in 2017-2019. The data analysis technique used in this study is multiple linear regression. The research result is known that partially variable profit sharing financing has no effect and is insignificant to net profit. In addition, partially variable lease financing has no effect and signifies net profit. While simultaneously variable profit sharing financing and lease financing have a significant influence on net profit.